2003
DOI: 10.1099/mic.0.26644-0
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity myo-inositol transport in Candida albicans: substrate specificity and pharmacology

Abstract: Inositol is considered a growth factor in yeast cells and it plays an important role in Candida as an essential precursor for phospholipomannan, a glycophosphatidylinositol (GPI)-anchored glycolipid on the cell surface of Candida which is involved in the pathogenicity of this opportunistic fungus and which binds to and stimulates human macrophages. In addition, inositol plays an essential role in the phosphatidylinositol signal transduction pathway, which controls many cell cycle events. Here, high-affinity my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 60 publications
2
49
0
Order By: Relevance
“…This classification is consistent with the close phylogenetic relationship of TbHMIT to plant and mammalian HMITs and more distant relationship to SMITs. In addition, the observed specificity of TbHMIT for myo-inositol, and certain inositol derivatives, is in line with previous studies on HMITs from L. donovani, T. cruzi, A. thaliana, and C. albicans (29,30,52,53), showing that other polyols and hexoses are not transported by HMITs, in contrast to SMITs, which readily transport glucose (54 -56). Our observation that scyllo-inositol and myo-inositol phosphate inhibited FIGURE 5.…”
Section: Discussionsupporting
confidence: 75%
“…This classification is consistent with the close phylogenetic relationship of TbHMIT to plant and mammalian HMITs and more distant relationship to SMITs. In addition, the observed specificity of TbHMIT for myo-inositol, and certain inositol derivatives, is in line with previous studies on HMITs from L. donovani, T. cruzi, A. thaliana, and C. albicans (29,30,52,53), showing that other polyols and hexoses are not transported by HMITs, in contrast to SMITs, which readily transport glucose (54 -56). Our observation that scyllo-inositol and myo-inositol phosphate inhibited FIGURE 5.…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, it was shown for human HepG2 liver cells that myoinositol and D-chiroinositol are transported by the same protein (Ostlund et al, 1996). Interestingly, however, in the yeast Candida albicans (Jin and Seyfang, 2003) and in the protozoan parasite Leishmania donovani (Mongan et al, 2004) transporters were identified that are highly specific for myoinositol, because no or only marginal competition by scyllo-or D-chiroinositol was seen. Moreover, for both inositol transport systems a 50% inhibition of myoinositol transport by phytate was observed.…”
Section: Atint2 Is a Plasma Membrane-localized H 1 Symporter That Difmentioning
confidence: 99%
“…The inositol uptake assay protocol was adapted in part from a protocol of Jin and Seyfang (15). The wild-type, itr1⌬/ITR1, itr1⌬/itr1⌬, and itr1⌬/itr1⌬::ITR1 strains were grown in YPD liquid cultures overnight at 30°C.…”
Section: Ino1mentioning
confidence: 99%
“…In addition, it has been shown previously that C. albicans has potent inositol transporter activity (15). It was demonstrated that the inositol transporter in C. albicans has an apparent K m of 240 Ϯ 15 M, and the transport system appears to be active and energy dependent (15). C. albicans inositol transport activity differs in substrate and cotransporter specificities from the human inositol-Na ϩ transporter.…”
mentioning
confidence: 99%
See 1 more Smart Citation